Tropical Agroforestry - Atangana, Alain; Khasa, Damase; Chang, Scott; Degrande, Ann.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
Agroforestry is recognized as a sustainable land-use management in the tropics, as it provides environmental-friendly ecosystems; it also provides people with their every day need for food and cash. Since the recognition of agroforestry as a science, curricula have been developed for agroforestry programs for undergraduate and graduate trainings in Universities. Therefore, there is an urgent need to develop and make available educational material. This textbook strives to provide up-to-date information on tropical agroforestry to serve as educational material in the tropical context. The authoritative textbook of Nair (1993) on agroforestry was published 18 years ago, and before the advent of tree domestication, an important agroforestry practice today. In addition, many other research activities, such as carbon sequestration and integrated pest management, have been included in the agroforestry agenda. This textbook is intended for agroforestry students, teachers, and practitioners.
Preface -- Acknowledgements -- Table of Contents -- List of Figures -- List of Tables -- Part I: Tropical Biomes, Land Use Issues and Introduction to Agroforestry Systems -- 1. Tropical biomes: classification and description -- 2. Major Land Use Issues in the Tropics, and the History of Agroforestry -- 3. Definitions and Classification of Agroforestry Systems -- 4. Major Agroforestry Systems of the Humid Tropics -- 5. Major Agroforestry Systems of the Semiarid Tropics -- 6. Participatory Domestication of New Crops using Agroforestry Techniques -- Part II: The Benefits and Services of Agroforestry Systems -- 7. Ecological Interaction and Productivity in Agroforestry Systems -- 8. Biological Nitrogen Fixation and Mycorrhizal Associations in Agroforestry -- 9. Agroforestry for Soil Conservation -- 10. Carbon Sequestration in Agroforestry Systems -- 11. Agroforestry and Biodiversity Conservation in Tropical Landscapes -- 12. Integrated Pest Management in Tropical Agroforestry -- 13. Diagnosis and Design (D & D) Approach and Participatory Rural Appraisal (PRA) -- 14. Experimental Design in Agroforestry -- 15. On-Farm Agroforestry Research -- 16. Economics in Agroforestry -- 17. Socio-Cultural Aspects of Agroforestry and Adoption -- 18. Tropical Agroforestry for Biofuels Production -- 19. Phytoremediation in Tropical Agroforestry -- 20. Agroforestry and the Carbon Market in the Tropics -- 21. Agroforestry Modeling.
Keywords: Life sciences; Agriculture; Forests and forestry; Life Sciences; Forestry; Agriculture